Arterial stiffness in obstructive sleep apnoea: Is there a difference between daytime and night‐time?. Issue 8 (5th July 2016) - Sarinc Ulasli, Sevinc; Sariaydin, Muzaffer; Ozkececi, Gulay; Gunay, Ersin; Halici, Bilal; Unlu, Mehmet
ABSTRACT: Background and objective: Obstructive sleep apnoea syndrome (OSAS) is a common chronic systemic disease in the general population, with known associated cardiovascular outcomes. We aimed to investigate arterial stiffness in OSAS patients and compare daytime and night‐time values with control subjects. Methods: A total of 104 patients undergoing investigation for OSAS with polysomnography also underwent pulse wave velocity (PWV) and augmentation index (AIx) measurements with Mobil‐O‐Graph for 24 h. Eighty‐two patients were found to have OSAS and 22 did not have OSAS and acted as controls. Results: PWV values of the 82 OSAS patients during the 24‐h period, both daytime and night‐time, were significantly higher than that of the control subjects. Moreover, night‐time levels of AIx were significantly higher in OSAS patients than control subjects ( P  = 0.025). PWV during night‐time was higher than daytime measurements in OSAS patients ( P  = 0.012). Apnoea hypopnoea index (AHI) was significantly correlated with PWV and AIx over 24 h ( P  = 0.0001, r  = 0.412; P  = 0.002, r  = 0.333, respectively). Positive correlations were also found between oxygen desaturation index (ODI) with PWV and AIx during the night ( P  = 0.0001, r  = 0.480; P  = 0.002, r  = 0.325, respectively). However, daytime AIx was not significantly correlated with ODI ( P  = 0.052, r  = 0.205). Conclusion: OSAS patients, without known cardiovascular disease, have increased PWV, indicating an increased arterial stiffness, compared with control subjects and correlations between AHI and arterial stiffness indices suggest increased arterial stiffness with increased disease severity. Therefore, arterial stiffness should be considered as a possible cause for cardiovascular complications in OSAS patients. Abstract : This study examines arterial stiffness over 24‐h periods, comparing daytime and night‐time values in obstructive sleep apnoea syndrome (OSAS) and control subjects. It demonstrates that OSAS patients had increased arterial stiffness parameters during the night and higher indices than control subjects.